2017
DOI: 10.1139/cgj-2017-0085
|View full text |Cite
|
Sign up to set email alerts
|

The Saint-Jude landslide of 10 May 2010, Quebec, Canada: Investigation and characterization of the landslide and its failure mechanism

Abstract: A landslide occurred on 10 May 2010, along the Salvail River, in the municipality of Saint-Jude, Quebec. Debris of the landslide was formed of clay having horst and graben shapes, typical of spreads in sensitive clays. A detailed investigation was carried out by the Ministère des Transports, de la Mobilité durable et de l'électrification des transports du Québec, in collaboration with Université Laval, with the objective of characterizing this landslide, determining the causes, and learning about its failure m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 13 publications
(28 reference statements)
6
42
0
Order By: Relevance
“…1). Leading to death of four people, the landslide had a retrogression distance of 80 m (defined as the distance from the initial crest of the slope to the final stable backscarp) and affected a section about 275 m long, parallel to the Salvail River and a total of 520,000 m 3 soil mass (Locat et al 2017). Both on-site and lab testing was carried out to obtain information on the stratigraphy and the geotechnical properties of the clays.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Leading to death of four people, the landslide had a retrogression distance of 80 m (defined as the distance from the initial crest of the slope to the final stable backscarp) and affected a section about 275 m long, parallel to the Salvail River and a total of 520,000 m 3 soil mass (Locat et al 2017). Both on-site and lab testing was carried out to obtain information on the stratigraphy and the geotechnical properties of the clays.…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of the Saint-Jude landslide is unknown. Slope stability analyses were performed in (Locat et al 2017;Locat et al 2011b) along the transect C-C′. In (Locat et al 2011b), it was shown that the initial failure based on drained analysis is very local whereas a large amount of clay would be disturbed if the slope failed under undrained conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations